1993
DOI: 10.1073/pnas.90.14.6439
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal colocalization of mRNAs for neurotrophins and their receptors in the developing central nervous system suggests a potential for autocrine interactions.

Abstract: Development and survival of neurons in the central nervous system are dependent on the activity of a variety of endogenous neurotrophic agents. Using combined isotopic and nonisotopic in situ hybridization histochemistry, we have found that subsets of neurons within the developing forebrain coexpress the mRNAs for both neurotrophins (nerve growth factor, brain-derived neurotrophic factor, and neurotrophin 3) and their receptors (p75NGFR, TrkA, and TrkB). The colocalization of mRNA for neurotrophin receptors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(157 citation statements)
references
References 43 publications
12
144
0
1
Order By: Relevance
“…Additionally, both BDNF and its TrkB receptor are often coexpressed in the same neuron (Kokaia et al 1993;Miranda et al 1993). These findings support the notion that BDNF exerts its actions by activating TrkB receptors, which trigger signal transduction pathways in both preand postsynaptic compartments, acting in both autocrine and paracrine fashions.…”
Section: Bdnf and Memory Consolidationsupporting
confidence: 76%
“…Additionally, both BDNF and its TrkB receptor are often coexpressed in the same neuron (Kokaia et al 1993;Miranda et al 1993). These findings support the notion that BDNF exerts its actions by activating TrkB receptors, which trigger signal transduction pathways in both preand postsynaptic compartments, acting in both autocrine and paracrine fashions.…”
Section: Bdnf and Memory Consolidationsupporting
confidence: 76%
“…Acheson et al, 1995). Previous authors have reported transcripts for neurotrophins and Trk receptors in patterns that seem to indicate auto/paracrine or anterograde neurotrophin signaling (Schecterson and Bothwell, 1992;Miranda et al, 1993). However, limited information is available on the mechanisms of action of neurotrophins in the CNS in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of NGF into neonatal rat pups increases ChAT activity within the striatum (Mobley et al, 1985). Striatal neurons during development express the low-affinity NGF receptor in rodents (Yan and Johnson, 1988;Lu et al, 1989) and humans (Kordower and Mufson, 1993), and striatal neurons express the high-affinity trkA receptor during rodent development (Miranda et al, 1993;Ringstedt et al, 1993) and in adulthood (Steininger et al, 1993). In the case of the striatum, it is likely that NGF acts within the striatum through interactions with the trkA receptor.…”
Section: Discussionmentioning
confidence: 99%